Dumbbell Schwannomas of the Internal Auditory Canal - Salzman, Karen L. (AJNR Am J Neuroradiol, 2001)
BACKGROUND AND PURPOSE: Benign tumors of the internal auditory canal (IAC) may leave the confines of the IAC fundus and extend into inner ear structures, forming a dumbbell-shaped lesion. It is important to differentiate dumbbell lesions, which include facial and vestibulocochlear schwannomas, from simple intracanalicular schwannomas, as surgical techniques and prognostic implications are affected. In this article, the imaging and clinical features of these dumbbell schwannomas are described. METHODS: A dumbbell lesion of the IAC is defined as a mass with two bulbous segments, one in the IAC fundus and the other in the membranous labyrinth of the inner ear or the geniculate ganglion of the facial nerve canal, spanned by an isthmus. Twenty-four patients with dumbbell lesions of the IAC had their clinical and imaging data retrospectively reviewed. Images were evaluated for contour of the mass and extension into the membranous labyrinth or geniculate ganglion. RESULTS: Ten of 24 lesions were facial nerve dumbbell lesions. Characteristic features included an enhancing “tail” along the labyrinthine segment of the facial nerve and enlargement of the facial nerve canal. Dumbbell schwannomas of the vestibulocochlear nerve (14/24) included transmodiolar (8/14), which extended into the cochlea, transmacular (2/14), which extended into the vestibule, and combined transmodiolar/transmacular (4/14) types. CONCLUSION: Simple intracanalicular schwannomas can be differentiated from transmodiolar, transmacular, and facial nerve schwannomas with postcontrast and high-resolution fast spin-echo T2-weighted MR imaging. Temporal bone CT is reserved for presurgical planning in the dumbbell facial nerve schwannoma group.